2011
DOI: 10.1021/ma201409t
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Polyanions Based on Poly(4,4-dimethyl-2-vinyl-2-oxazoline-5-one-co-methacrylic acid)

Abstract: The formation of reactive polyanions by semibatch copolymerization of 4,4-dimethyl-2-vinyl-2-oxazoline-5one (VDMA) and methacrylic acid (MAA) by both free radical and photoinduced radical polymerization is described. The reactivity ratios of these two monomers were determined to be 1.36 and 0.41 for r 1 (VDMA) and r 2 (MAA), respectively, using 1 H NMR spectroscopy. During the free radical copolymerization of a 50:50 VDMA:MAA copolymer (PMV 50 ) in anhydrous DMSO or THF at 60 °C, up to 40% of the azlactone gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 31 publications
3
23
0
Order By: Relevance
“…The reactivity ratios of VDMA and MAA measured here for photo‐initiated polymerization at ∼10 °C in DMSO ( r 1 (VDMA) = 1.45 and r 2 (MAA) = 0.57) are in good agreement with our previously reported values ( r 1 (VDMA) = 1.36 and r 2 (MAA) = 0.41),13 obtained using the same analysis method but thermally initiated polymerization at 60 °C with AIBN, also in DMSO.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The reactivity ratios of VDMA and MAA measured here for photo‐initiated polymerization at ∼10 °C in DMSO ( r 1 (VDMA) = 1.45 and r 2 (MAA) = 0.57) are in good agreement with our previously reported values ( r 1 (VDMA) = 1.36 and r 2 (MAA) = 0.41),13 obtained using the same analysis method but thermally initiated polymerization at 60 °C with AIBN, also in DMSO.…”
Section: Resultssupporting
confidence: 92%
“…While the hydrolysis of residual azlactones helps avoid immunogenic protein binding, hydrolysis half‐lives that are too short can limit the extent of crosslinking achievable. Our previously reported p(VDMA‐ co ‐MAA) 50:50 copolymer had a hydrolysis half‐life of about 30 min in (4‐(2‐hydroxyethyl)‐1‐piperazine ethanesulfonic acid) (HEPES) buffered saline at about pH 7.4 13. That work also showed that photo‐initiated copolymerization at room temperature could be used to suppress an undesirable side‐reaction between the azlactone and MAA groups during copolymerization.…”
Section: Introductionmentioning
confidence: 91%
“…This ratio gives quantitative information on the propensity of an active center to react with either of the monomers; and when using terminal models, it is assumed to depend on the terminal monomeric unit. The reactivity ratios for the copolymerization were determined using Aguilar's method (eqs S1 and S2, terminal model, Supporting Information) based on the in situ 1 H‐NMR experiments (Fig. ) and solved via a nonlinear least square regression method using [DMAm] and [NIPAM] as variables.…”
Section: Resultsmentioning
confidence: 99%
“…Their study determined r NIPAM and r DMAm using a linear least square method (extended Kelen‐Tudos) for analyzing data obtained from batch experiments at high monomer conversions; whereas this study was based on in situ 1 H‐NMR data fitted via a nonlinear least square approach. The in situ 1 H‐NMR technique will provide better representation of the instantaneous monomers’ concentrations, while the nonlinear least square method is widely accepted as the most reliable method for determining reactivity ratios . Besides, the defining sequence of the copolymers as ideal with a tendency toward a pattern ( r DMAm × r NIPAM = 0.59–0.66), an expected implication is a compositional drift with tails richer in NIPAM units after much of the other monomer is consumed.…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that either cross‐linked shells or cross‐linked cores are obtainable by adjusting the molar mass of the cross‐linker. Approaches based on chemical cross‐linking through complementary reactive groups attached to two oppositely charged polyelectrolytes were also investigated . Similarly, microbeads were prepared by ionotropic gelation of a combination of Ca‐alg and sericin as inner core followed by coating with chitosan and further cross‐linking with genipin .…”
Section: Hydrogels For Cell Microencapsulationmentioning
confidence: 99%